Effective workload management in child welfare: Understanding the relationship between caseload and workload. (13th March 2019) - Kim, Jangmin; Yi, Eun‐Hye; Pierce, Barbara; Hall, James
Abstract: A common assumption in public social service organizations is that workload may be positively associated with caseload. However, few empirical studies have examined what specific characteristics of caseload affect caseworkers' workloads in the child welfare system. This study attempts to address this gap by identifying specific individual and regional factors that influence both subjective and objective dimensions of workloads. Survey data were collected from 1, 244 caseworkers at one public child welfare agency in a Midwestern state in the United States. The data indicated that both perceptions of unmanageable workloads and self‐reported overtime work were significantly higher when caseworkers had a greater number of cases than the state caseload standard for the investigations units and worked with at least two different types of cases simultaneously (e.g., working with both investigation and ongoing service cases). Additionally, sufficient staffing numbers to meet caseload demands at the regional level significantly decreased the odds ratio of having to do overtime work. The major findings suggest that the objective and subjective dimensions of workload vary by individual‐ and regional‐level variables. Practice implications are discussed for effective and efficient workload management in the public child welfare system.